2000
DOI: 10.1515/znc-2000-3-425
|View full text |Cite
|
Sign up to set email alerts
|

Antinematodal Activity of Some Tropical Rainforest Plants against the Pinewood Nematode, Bursaphelenchus xylophilus

Abstract: Sixty five methanolic extracts of Sumatran rainforest plants representing 63 species of 21 families were as sayed in vivo for antinematodal activity against Bursa phelenchus xylophilus using our cotton ball-fungal mat method. Extracts of 27 plants species from 14 families exhibited antinematodal activity, while 37 species were inactive. Among them, three extracts of Bischofia javanica, Knema hookeriana and Areca catechu exhibited very strong activity at minimum effective dose (M ED ) of 0.7 mg/cotton ball (mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Detailed literature review indicated that various classes of phytochemicals have been identified in different parts of M. malabathricum such as fatty acids and aliphatic constituents (Dinda & Saha 1986a, Dinda & Saha 1986b, Dass & Kotoky 1988, sterols (Manzoor-I-Khuda et al 1981), phenolic acids (Lowry 1968), flavonoids and their glycosides (Dinda & Saha 1988, Mohandoss & Ravindran 1993, Wong et al 2012, tannins (Yoshida et al 1992a(Yoshida et al , 1992b, anthocyanins (Lowry 1976), amino acids (Dinda & Saha 1985) and so on. Different parts of the plant have been shown to exert diverse biological activities like antibacterial and antifungal (Grosvenor et al 1995, Wiart et al 2004, Johnny et al 2010, Maji et al 2010), cytotoxic (Susanti et al 2007 and antiviral (Nazlina et al 2008, Lohezic-Le Devehat et al 2002, antiparasitic (Alen et al 2000), antioxidant (Susanti et al 2007, anticoagulant (Manicam et al 2010), platelet-activating factor inhibitory (Jantan et al 2005), wound healing (Sunilson et al 2008), anti-ulcer (Hussain et al 2008), anti-diarrheal (Sunilson et al 2009), anti-nociceptive (Sulaiman et al 2004), and anti-pyretic (Zakaria et al 2006) at different concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed literature review indicated that various classes of phytochemicals have been identified in different parts of M. malabathricum such as fatty acids and aliphatic constituents (Dinda & Saha 1986a, Dinda & Saha 1986b, Dass & Kotoky 1988, sterols (Manzoor-I-Khuda et al 1981), phenolic acids (Lowry 1968), flavonoids and their glycosides (Dinda & Saha 1988, Mohandoss & Ravindran 1993, Wong et al 2012, tannins (Yoshida et al 1992a(Yoshida et al , 1992b, anthocyanins (Lowry 1976), amino acids (Dinda & Saha 1985) and so on. Different parts of the plant have been shown to exert diverse biological activities like antibacterial and antifungal (Grosvenor et al 1995, Wiart et al 2004, Johnny et al 2010, Maji et al 2010), cytotoxic (Susanti et al 2007 and antiviral (Nazlina et al 2008, Lohezic-Le Devehat et al 2002, antiparasitic (Alen et al 2000), antioxidant (Susanti et al 2007, anticoagulant (Manicam et al 2010), platelet-activating factor inhibitory (Jantan et al 2005), wound healing (Sunilson et al 2008), anti-ulcer (Hussain et al 2008), anti-diarrheal (Sunilson et al 2009), anti-nociceptive (Sulaiman et al 2004), and anti-pyretic (Zakaria et al 2006) at different concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils have long been known to have significant biological activities. Recent studies have shown that some essential oils appear to have good nematicidal activity against the PWN under laboratory conditions [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…By using this method, methanolic extracts of 63 tropical rainforest plants were assessed and 27 plants were proved to contain active component(s) against the phytopathogenic nematode, Bursaphelenchus xylophilus. Among them, the extract of the sap of Knema hookeriana was shown to have pronounced activity (Alen et al, 2000). A literature survey revealed that the isolation work of antinematodal compounds from this species has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%